EFFECT FREQUENCY FRYINGONPEROXIDE NUMBER TO COOKING OIL IN PACKAGING - AGUSTINA WILHELMINA DJUMA (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Cooking oil is often used by people to the frying process repeated so that cause demage that is caused by oxidation and polymerization. Peroxide number is one of the parameters to determine the level of damage to oil. Oxidation reaction in the oil begins with the formation of free radicals is accelerated by light, heat, metals (iron and copper). The purpose of this study was to determine the effect on the frequency of frying to peroxide number on the packaging oil. Type of study is a Quasi-experiment. The method used to measure peroxide number is iodometric titration method. After that the data obtained were analyzed using Pearson correlation test and followed by linear regression analysis. Based on the results obtained on samples that have not been used as much peroxide levels Mek 0.80 O2 / Kg, the first frying peroxide number were 1.52 Mek O2 / Kg, the second frying peroxide levels Mek 1.70 O2 / Kg, on the third frying peroxide levels were 1.74 Mek O2 / Kg, the fourth frying peroxide levels were 1.94 Mek O2 / Kg and the fifth frying peroxide levels were 2.39 MekO2/Kg. Pearson correlation test results obtained by the value of r = 0.943 with a regression equation was y = 0.761 + 0.265 (x). These results indicate that there is a strong positive relationship between the frequency of the frying and peroxide. The higher the frequency of the frying, the higher the peroxide number on cooking oil.